Convective Heat Transfer Performance Of Staggered Heat Sink Arrays Fabricated By Selective Laser Melting - Wong, Kin Keong (2016)
In this paper, the forced convective heat transfer performances of heat sinks produced by Selective Laser Melting (SLM) were experimentally investigated. In total, three staggered array heat sinks were fabricated by SLM of aluminium alloy AlSi10Mg powders in Future of Manufacturing Lab 1, Singapore Centre for 3D Printing. The heat sinks which are of different fin geometries, namely, circular, rectangular rounded and aerofoil shaped fins (NACA 4424), were tested in a rectangular air flow channel. The flow channel was designed with large wall-to-fin clearance ratios such that pressure differences across the various heat sinks measured under similar flow conditions are negligible. Experiments performed for mass flow rates ranging from 0.00554 kg/s to 0.0387 kg/s showed that the heat transfer performances of the aerofoil and rectangular rounded heat sinks exceeded those of the circular heat sink. The highest enhancement in heat transfer coefficient of 33.9% was recorded with the rectangular round heat sink as compared to the circular heat sink at mass flow rate 0.0387 kg/s whereas the highest enhancement in heat transfer coefficient of 28.7% was achieved with aerofoil at mass flow rate 0.00554 kg/s. It is suggested that the aerodynamically designed aerofoil shapes resulted in minimal hydraulic resistance which allowed larger air flow rate between the fins with insignificant bypass, thereby improving the heat transfer performances of the heat sinks. On the other hand, vortex shedding due to the blunt edges of the rounded rectangular heat sink was postulated to have resulted in the enhanced heat transfer.